La ignorancia deliberada en la fórmula legislativa “debía presumir” en el delito de lavado de activos en el Perú - Artica Taboada, Raul Martin (2024)
This article examines the concept of deliberate ignorance in the criminal sphere and its applicability to the crime of money laundering in Peru, particularly in relation to the legislative formula ‘should be presumed’. Through the analysis of malice and its different manifestations, doctrinal tensions are explored between the classic conception of malice and the possibility of imputing criminal liability to individuals who, without direct knowledge of the unlawfulness of their conduct, have decided to remain in a state of intentional ignorance.Case law and doctrinal precedents are studied, both in comparative and national law, to determine whether deliberate ignorance can be equated to malice aforethought and, consequently, used as a criterion of subjective attribution in the context of the crime of money laundering. In particular, the article analyzes how the absence of an express definition of malice in the Peruvian Criminal Code allows for a flexible interpretation that could admit deliberate ignorance as a form of criminal imputation.The article concludes that the application of deliberate ignorance should not be based on the requirement of actual knowledge of the offense, but on the commitment to know that the subject has consciously avoided. Thus, it is suggested that the incorporation of this figure in the interpretation of the criminal offense would contribute to strengthen the prosecution of money laundering, preventing the agents from benefiting from feigned ignorance as a strategy of impunity.